Urgensi Pendekatan Humanistik-Religius dalam Pembinaan Santri pada Pesantren Darul Huffadh Tuju-Tuju Kecamatan Kajuara Kabupaten Bone - Anwar, Anwar (JURNAL AL-QAYYIMAH, 2019)
This article is about the urgency of humanistic-religious approach in coaching students at the Pesantren Darul Huffadh Tuju-Tuju Sub-district of Bone Regency. This research uses field research located in the boarding school Tuju-Tuju Kajuara Bone. The approach used is pedagogical, psychological and sociological. Qualitative descriptive analysis. The results showed that the humanistic-religious form in the development of students at Pesantren Darul Huffadh Tuju-Tuju among others through (1) curricular learning in the application of RPP, methods, materials and media. (2) Extracurricular learning with the form of application of Scouts, PMR, UKS, KIR, Rohis and sports. (3) Culture of Pesantren by the way; Reading the Koran, praying in congregation, greetings to the teachers. The form of coaching applied with the purpose of the creation of a process and pattern of coaching that always put human beings as having all potential, whether the potential of physical, psychic, and spiritual. As for the humanistic-religious urgency in the coaching of students in the school of Islamic Pesantren Darul Huffadh Tuju, it is a dignified interaction pattern, a coaching model that is interactive, creative, innovative, active and enjoyable, and humanized sanctions.Artikel ini adalah tentang urgensi pendekatan humanistik-keagamaan dalam pembinaan siswa di Pesantren Darul Huffadh Tuju-Tuju, Kabupaten Bone. Penelitian ini menggunakan penelitian lapangan yang berlokasi di pondok pesantren Tuju-Tuju Kajuara Bone. Pendekatan yang digunakan adalah pedagogis, psikologis dan sosiologis. Analisis deskriptif kualitatif. Hasil penelitian menunjukkan bahwa bentuk humanistik-religius dalam pengembangan siswa di Pesantren Darul Huffadh Tuju-Tuju antara lain melalui (1) pembelajaran kurikuler dalam penerapan RPP, metode, bahan dan media. (2) Pembelajaran ekstrakurikuler dengan bentuk aplikasi Pramuka, PMR, UKS, KIR, Rohis dan olahraga. (3) Kebudayaan Pesantren; Membaca Alquran, shalat berjamaah, menyapa para guru. Bentuk pembinaan diterapkan dengan tujuan terciptanya suatu proses dan pola pembinaan yang selalu menempatkan manusia sebagai memiliki semua potensi, baik potensi fisik, psikis, maupun spiritual. Adapun urgensi humanistik-agama dalam pembinaan siswa di sekolah Pesantren Islam Darul Huffadh Tuju, itu adalah pola interaksi yang bermartabat, model pelatihan yang interaktif, kreatif, inovatif, aktif dan menyenangkan, dan sanksi yang dimanusiakan.